2019
DOI: 10.14302/issn.2374-9431.jbd-19-2788
|View full text |Cite
|
Sign up to set email alerts
|

L162v Polymorphism of Par-Α Gene, A603g Polymorphism of Tissue Factor Gene and Risk of Coronary Heart Disease in Russian Population

Abstract: Purpose The goal of this study is to determine the association of L162V polymorphism of PPAR-alpha gene, A603G polymorphism of tissue factor gene and the risk of coronary heart disease development in Russian population. Materials and Methods A clinical and genetic study of 414 patients with CHD and 220 people of comparable age without CHD which amounted to a control group was performed. L162L and L162V genotypes of L162V polymorphism of PPAR-α gene, A603A, A603G and G603G genotypes of A603G polymorphism of tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Other studies in the literature have previously examined the PPAR alpha L162V polymorphism in patients with CHD and MI. In some studies, the L161V polymorphism was found to be a risk factor for CHD, although it was not found to be a risk factor in others [ 16 , 27 - 30 ]. Reinhard et al found no relationship between L162V polymorphism and MI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in the literature have previously examined the PPAR alpha L162V polymorphism in patients with CHD and MI. In some studies, the L161V polymorphism was found to be a risk factor for CHD, although it was not found to be a risk factor in others [ 16 , 27 - 30 ]. Reinhard et al found no relationship between L162V polymorphism and MI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sergeeva et al investigated the L162V polymorphism in CHD patients and a control group. PPAR-alpha gene L162V genotype and V allele carriers were found to have a 2.21-fold increased risk of suffering from CHD [ 30 ]. Similarly, Qian et al suggested that having a V allele in L162V polymorphisms increases the risk of CHD [ 16 ].…”
Section: Discussionmentioning
confidence: 99%